2021
DOI: 10.3389/fspor.2021.692632
|View full text |Cite
|
Sign up to set email alerts
|

Reusing Stadiums for a Greener Future: The Circular Design Potential of Football Architecture

Abstract: Since the turn of the new Millennium, there has been an increase in efforts to build environmental-friendly sports arenas around the world. Fuelled by large sporting events like the 2000 Sydney Olympics, the ‘Green Games,’ and the 2006 FIFA World Cup in Germany, stadium architecture has become a vehicle for this trend. So far, the emphasis has primarily been on new arenas, in line with the widespread belief in international architecture of the 2000s that older buildings are less energy-efficient by default. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In this study, we utilize four diverse datasets encompassing crucial information related to stadium construction, energy consumption, carbon emissions, and other relevant factors. Through a rigorous evaluation process, we compare the performance of our model against several state-of-the-art methods, including Bunds et al (Bunds et al, 2019), Kucukvar et al (Kucukvar et al, 2021), Al-Hamrani et al (Al-Hamrani et al, 2021), Wergeland et al (Wergeland and Hognestad, 2021), Osorio et al (Osorio et al, 2022), and Elnour et al (Elnour et al, 2022a). Across all datasets and evaluation metrics, our proposed model consistently outperformed the compared methods.…”
Section: Experimental Results and Analysismentioning
confidence: 93%
“…In this study, we utilize four diverse datasets encompassing crucial information related to stadium construction, energy consumption, carbon emissions, and other relevant factors. Through a rigorous evaluation process, we compare the performance of our model against several state-of-the-art methods, including Bunds et al (Bunds et al, 2019), Kucukvar et al (Kucukvar et al, 2021), Al-Hamrani et al (Al-Hamrani et al, 2021), Wergeland et al (Wergeland and Hognestad, 2021), Osorio et al (Osorio et al, 2022), and Elnour et al (Elnour et al, 2022a). Across all datasets and evaluation metrics, our proposed model consistently outperformed the compared methods.…”
Section: Experimental Results and Analysismentioning
confidence: 93%
“…The case of innovative shipping container stadium [33] Investigating alternative development strategies for sport arenas based on active and passive systems [34] Modern Stadium Design: an adaptive renovation or urban renewal. [35] Research on the Indoor Physical Characteristic of the Ceiling of China National Aquatics Center under the Demand of Olympic Games [15] Reusing Stadiums for a Greener Future: The Circular Design Potential of Football Architecture [36] Rwanda Cricket Stadium: Seismically stabilised tile vaults [37] The Object-Oriented Politics of Stadium Sustainability: A Case Study of SC Freiburg [38] Using Simulation-Based Modeling to Evaluate Light Trespass in the Design Stage of Sports Facilities [39] Water savings and reduction of costs through the use of a dual water supply system in a sports facility [40]…”
Section: Paper Title Referencementioning
confidence: 99%
“…The urban construction sector is among the most evident sectors that contribute to negative environmental impacts (Kucukvar and Tatari, 2012 , 2013 ; Onat et al, 2014 ) and research has shown that CE concepts such as the adaptive repurposing of existing, abandoned, and historical buildings, is beneficial for the environment and neighborhood revitalization (Bullen and Love, 2010 ; Baker et al, 2017 ; Foster, 2020 ). Drawing from concepts such as adaptive reuse and maintenance architecture, Wergeland and Hognestad ( 2021 ) concluded football (soccer) stadia have potential for circularity if the broader sports community becomes more willing to preserve architectural legacy. To do so, they argued further investment in stadium restoration is required to limit demolition of historic stadia, while legislative changes are necessary to make it easier to modify existing sports venues.…”
Section: Shadow Stadia and The Circular Economymentioning
confidence: 99%
“…One innovative approach is moving toward emerging circular sustainability and construction methods. Wergeland and Hognestad ( 2021 ) recently emphasized green strategies and perspectives such as the circular economy that could extend the lifecycle of existing football stadia. Bengtsson et al ( 2018 ) argued that the circular economy, defined through specific actions and practices such as eco-design, reuse, refurbishment, remanufacturing (Nasr and Thurston, 2006 ), repair and product sharing (Chertow and Ehrenfeld, 2012 ), can contribute to reaching the social, economic, and environmental targets set forth by the 2030 Agenda's Sustainable Development Goals.…”
Section: Introductionmentioning
confidence: 99%